USM CONTINUES THE TRADITION OF CELEBRATING INTERNATIONAL STUDENTS - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, July 2015 Universiti Sains Malaysia (USM) continues the tradition of celebrating its students and staff who hail from different countries with its breakingoffast programme and holding the upcoming Aidilfitri celebrations.